Measurement of jet substructure observables in t(t)over-bar events from proton-proton collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
A measurement of jet substructure observables is presented using t (t) over bar events in the lepton + jets channel from proton-proton collisions at root s = 13 TeV recorded by the CMS experiment at the LHC, corresponding to an integrated luminosity of 35.9 fb(-1). Multiple jet substructure observables are measured for jets identified as bottom, light-quark, and gluon jets, as well as for inclusive jets (no flavor information). The results are unfolded to the particle level and compared to next-to-leading-order predictions from POWHEG interfaced with the parton shower generators PYTHIA 8 and HERWIG 7, as well as from SHERPA 2 and DIRE 2. Avalue of the strong coupling at the Z boson mass, alpha(S)(m(Z)) = 0.115(-0.013)(+0.015), is extracted from the substructure data at leading-order plus leading-log accuracy.
Keywords: PLUS PLUS; FRAGMENTATION; QCD; DISTRIBUTIONS; ANNIHILATION; MOMENTS; QUARKS; MODEL; HERA